Impact of Bank Specific and Macroeconomic Determinants on Banks Liquidity: An Empirical Study on Listed Commercial Banks in Bangladesh - Tasnova, Nishat (Finance & Economics Review, 2022)
Purpose This study examines the influences of bank-specific and macroeconomic determinants on liquidity on 29 listed commercial banks of Bangladesh. Methods To analyze the relationship, this study performs Pooled Ordinary Least Square method, fixed and random effect estimates, and implemented GLS random effect method on strongly balanced panel dataset over 2014 to 2019. Capital adequacy, nonperforming loans, and profitability are considered bank-specific factors while GDP, Monetary policy interest rate, and Interest rate spread are considered the macroeconomic factors. Results Business cycle and monetary policy interest rate inversely affected bank liquidity. Contrary, bank liquidity has a positive association with profitability, nonperforming loans, capital adequacy, and interest rate spread. According to the findings, capital adequacy and business cycle have a significant impact on liquidity. Implications This study has significant implications for bankers, consumers, and policymakers. The banking sector of Bangladesh will highly be benefited from this research as this paper critically analyzes the determinants of banks' liquidity risk. This research will help the banks and other financial institutions to understand the effect of capital adequacy, nonperforming loans on liquidity in the Bangladeshi context. This study infers that banks need to monitor the factors cautiously to avoid the liquidity crisis in the future. Originality There are a few studies that examine these determinants with liquidity in the Bangladeshi context. This remarks the significance of the present paper as this study put an attempt to analyze bank-specific and macroeconomic determinants with bank liquidity in the Bangladeshi context has been conducted within a limited scope.